The Effect of ANSIVI (Animation and Simulation Video) Choking Management on Parents' Ability to Provide First Aid for Choking - Pria Wahyu Romadhon Girianto (International Journal of Health and Medicine, 2026)
Choking is a dangerous thing for children, especially children with special needs who require proper handling, and parents as the closest people to the child must have first aid skills for choking. The purpose of this study is to determine the effect of ANSIVI (Animation and Simulation Video) Choking Management on parents' ability in first aid for choking. The research design was a pre-experimental design with a one-group pretest-posttest approach without control. The purposive sampling technique obtained 36 respondents. The research instrument used an observation sheet for first aid for choking. The statistical test was the Wilcoxon Signed Rank Test with α 0.05. The results of the study before being given the ANSIVI (Animation and Simulation Video) Choking Management intervention showed that all (100%) respondents had insufficient ability, and after the intervention the majority (52.8%) of respondents had sufficient ability. The results of the statistical analysis obtained a p-value of 0.013 < α 0.05, so there is an effect of ANSIVI (Animation and Simulation Video) choking management on parents' ability in first aid for choking. The ANSIVI method (Video Animation and Simulation) combines two methods so that it is more interesting, interactive, and effective because the video is captured by the eyes and ears and then will be detected and converted into signals to the optic nerve and auditory nerve and forwarded to the brain, program area, and frontal area to be associated so that it will affect the respondent's ability. The ANSIVI method can be used in education for all parents and school residents as a first aid effort for choking, especially for children with special needs.